Hybrid Genetic Algorithm-Support Vector Machine Technique for Power Tracing in Deregulated Power Systems - Mustafa, Mohd Wazir; Sulaiman, Mohd Herwan; Khalid, Saifulnizam Abd.; Shareef, Hussain (IntechOpen, 2012)
None